Working for peace and justice : memoirs of an activist intellectual - Wittner, Lawrence S. (Knoxville : University of Tennessee Press, 2012)
A longtime agitator against war and social injustice, Lawrence Wittner has been tear-gassed, threatened by police with drawn guns, charged by soldiers with fixed bayonets, spied upon by the U.S. government, arrested, and purged from his job for political -reasons. To say that this teacher-historian-activist has led an interesting life is a considerable understatement. In this absorbing memoir, Wittner traces the dramatic course of a life and career that took him from a Brooklyn boyhood in the 1940s and '50s to an education at Columbia University and the University of Wisconsin to the front lines of peace activism, the fight for racial equality, and the struggles of the labor movement. He details his family background, which included the bloody anti-Semitic pogroms of late-nineteenth-century Eastern Europe, and chronicles his long teaching career, which comprised positions at a small black college in Virginia, an elite women's liberal arts college north of New York City, and finally a permanent home at the Albany campus of the State University of New York. Throughout, he packs the narrative with colorful vignettes describing such activities as fighting racism in Louisiana and Mississippi during the early 1960s, collaborating with peace-oriented intellectuals in Gorbachev's Soviet Union, and leading thousands of antinuclear demonstrators through the streets of Hiroshima. As the book also reveals, Wittner's work as an activist was matched by scholarly achievements that made him one of the world's foremost authorities on the history of the peace and nuclear disarmament movements--a research specialty that led to revealing encounters with such diverse figures as Norman Thomas, the Unabomber, Zbigniew Brzezinski, Caspar Weinberger, and David Horowitz. A tenured professor and renowned author who has nevertheless lived in tension with the broader currents of his society, Lawrence Wittner tells an engaging personal story that includes some of the most turbulent and significant events of recent history.
1. Family Background; 2. Brooklyn Boyhood, 1941-1958; 3. College Days, 1958-1962; 4. Graduate School, 1962-1967; 5. A Young Faculty Member, 1967-1972; 6. Overseas Exile, 1972-1974; 7. Grappling with Issues of Work and Love, 1974-1980; 8. An Activist Academic, 1981-1989; 9. A National and International Figure, 1990-2001; 10. Growing Old, but Not Gracefully, 2001-2011; 11. In Retrospect; Other Books by Lawrence Wittner.
Print version record.
"Other books by Lawrence Wittner": page 253.
English.
JSTOR
Keywords: Wittner, Lawrence S; State University of New York at Albany -- Faculty -- Biography; Wittner, Lawrence S; State University of New York at Albany; Intellectuals -- United States -- Biography; Political activists -- United States -- Biography; Pacifists -- United States -- Biography; Scholars -- United States -- Biography; Historians -- United States -- Biography; Student movements -- United States -- History -- 20th century; Peace movements -- History -- 20th century; Social justice -- History -- 20th century; Intellectuels -- États-Unis -- Biographies; Activistes -- États-Unis -- Biographies; Pacifistes -- États-Unis -- Biographies; Savants -- États-Unis -- Biographies; Historiens -- États-Unis -- Biographies; Mouvements étudiants -- États-Unis -- Histoire -- 20e siècle.; Mouvements pacifistes -- Histoire -- 20e siècle.; Justice sociale -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Social Classes; BIOGRAPHY & AUTOBIOGRAPHY -- General; Historians; Intellectuals; Pacifists; Peace movements; Political activists; Scholars; Social justice; Student movements; Universities and colleges -- Faculty; United States; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; 1900-1999; Autobiography; autobiographies (literary genre); Autobiographies; Biographies; History; Autobiographies; Autobiographies